Peningkatan kemampuan berbicara (speaking) siswa melalui metode role play pada mata pelajaran bahasa inggris - kamilah, Rohmatul (Maliki Interdisciplinary Journal, 2025)
This study examines the effectiveness of using the role play method in improving English speaking skills among adolescent students. The approach used is a qualitative descriptive study with data collection through observation, interviews, and documentation of learning activities in the classroom. The results show that the role play method has a positive impact on improving students’ speaking skills, including courage, vocabulary mastery, and understanding of sentence structure in real contexts. In addition, this method increases students’ motivation and confidence in using English actively and communicatively. The effectiveness of the role play method is influenced by the relevance of the scenario used as well as the fun and collaborative learning atmosphere. Therefore, it is recommended that teachers choose scenarios that are appropriate to the learning material and combine role play with discussion to strengthen students’ understanding. This research emphasizes the importance of creating an interactive and supportive learning environment so that students can develop their English speaking skills optimally.